Adsorption of Cd(ii) from aqueous solution by biogenic selenium nanoparticles. Issue 18 (5th February 2016) - Yuan, Fanghui; Song, Chao; Sun, Xuefei; Tan, Linrui; Wang, Yunkun; Wang, Shuguang
Abstract : BioSeNPs, which were produced by aerobic granular sludge in a sequencing batch reactor, could be used to remove cadmium from aqueous solution with high efficiency. Abstract : Biogenic selenium nanoparticles (BioSeNPs), which were produced by aerobic granular sludge in a sequencing batch reactor (SBR), were used to remove cadmium from aqueous solution. Batch experiments were carried out to investigate the effect of contact time, initial solution pH and adsorbent dosage on adsorption. The Langmuir model was more suitable to describe the adsorption process than the Freundlich model, with a monolayer maximum adsorption capacity of 59.7 mg g −1 for Cd(ii ) adsorption by the BioSeNPs. The isotherm data were also well described by the Temkin model, which further supported that Cd(ii ) adsorption was a chemisorption process. The adsorption kinetics data were well described by the pseudo-second-order kinetic model with r 2 values exceeding 0.999. The overall rate process was influenced by both external mass transfer and intraparticle diffusion, but was mainly controlled by intraparticle diffusion. The negative values of Δ G 0 and Δ H 0 indicated that the adsorption process was spontaneous and exothermic. Energy dispersive X-ray spectrometry (EDS) analysis confirmed that Cd(ii ) was adsorbed onto BioSeNPs. After being loaded with Cd(ii ), the BioSeNPs had less negative zeta potential values and no obvious change in the isoelectric point was observed. The Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) analysis indicated that the removal of Cd(ii ) was a complicated process, in which electrostatic attraction and surface complex formation were involved. The results demonstrated that BioSeNPs could be used to remove cadmium from aqueous solution with high efficiency.